Introduction to psychology - Stangor, Charles; Walinga, Jennifer; BC Open Textbook Project; BCcampus (BCcampus, BC Open Textbook Project, 2014)
"This book is designed to help students organize their thinking about psychology at a conceptual level. The focus on behaviour and empiricism has produced a text that is better organized, has fewer chapters, and is somewhat shorter than many of the leading books. The beginning of each section includes learning objectives; throughout the body of each section are key terms in bold followed by their definitions in italics; key takeaways, and exercises and critical thinking activities end each section."--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on version viewed on BCcampus OpenEd website; title from pdf title page.
Keywords: Psychology -- Textbooks; Electronic books